PENYALAHGUNAAN KEADAAN SEBAGAI ALASAN PEMBATALAN PERJANJIAN INVESTASI - Nicholas, Ferdinand; Soemartono, Raden Mas Gatot Prasetyo (Legal Standing : Jurnal Ilmu Hukum, 2024)
Business activities often involve third parties, including banks, which are established to improve the lives of individuals by providing an effective and efficient payment system. However, banks can sometimes get involved in legal issues, especially when they exploit circumstances involving individuals in vulnerable positions, such as those in prison. This study aims to investigate the concept of abuse of circumstances as a legitimate reason for the cancellation of an agreement. Utilizing normative research methods, this study seeks to examine the dynamics of law by examining legal rules, principles and legal doctrines. The results of this study show that a defect in will in an agreement can warrant cancellation by the injured party if it can be shown that there was an abuse of circumstances. In addition, custodian banks should be held accountable for losses incurred due to their actions or omissions in such situations. By clarifying legal responsibilities, this study emphasizes the need for banks to exercise due diligence and ethical practices in their transactions, especially with vulnerable individuals. The originality of this study lies in its specific focus on the application of the concept of abuse of circumstances in the legal relationship between banks and individuals in vulnerable situations, such as prisoners. While many legal studies focus on the general aspects of contractual liability, this study highlights an often overlooked legal gap regarding the protection of individuals who may not have the capacity to understand or reject onerous provisions in an agreement.